2015
DOI: 10.1155/2015/276850
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Myc and Mediators of Inflammation in Chronic Liver Diseases

Abstract: Most chronic liver diseases (CLDs) are characterized by inflammatory processes with aberrant expressions of various pro- and anti-inflammatory mediators in the liver. These mediators are the driving force of many inflammatory liver disorders, which often result in fibrosis, cirrhosis, and liver tumorigenesis. c-Myc is involved in many cellular events such as cell growth, proliferation, and differentiation. c-Myc upregulates IL-8, IL-10, TNF-α, and TGF-β, while IL-1, IL-2, IL-4, TNF-α, and TGF-β promote c-Myc e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 136 publications
2
52
0
Order By: Relevance
“…CLD can be triggered by numerous factors including diet, alcohol, viral infection and genetic disorders, which share common features including excessive inflammation 2 , dysregulated transforming growth factor (TGFβ) signalling 3 and dramatic disruption in the vascular architecture of the liver 4, 5 . Recent studies have revealed that disruption of endothelial cell (EC) homoeostasis can initiate tissue damage and fibrosis 68 .…”
Section: Introductionmentioning
confidence: 99%
“…CLD can be triggered by numerous factors including diet, alcohol, viral infection and genetic disorders, which share common features including excessive inflammation 2 , dysregulated transforming growth factor (TGFβ) signalling 3 and dramatic disruption in the vascular architecture of the liver 4, 5 . Recent studies have revealed that disruption of endothelial cell (EC) homoeostasis can initiate tissue damage and fibrosis 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous findings reporting that IL-8 and IL-1β are targets of β-catenin 28,29 and c-myc. 30,31 Interestingly, IL-8-KO and IL-1β-KO IC clones, characterized by nearly undetectable levels of cytokines mRNA (Figs. 6b and 6c) and protein (Figs.…”
Section: The Gsk3β/β-catenin/c-myc Axis Upregulates Abcb5 In Mpm Icsmentioning
confidence: 99%
“…Zhang et al found that the TF E2F1 was a new profibrotic factor that could facilitate the progression of liver fibrosis through the Egr-1/SHP/EID1 network[17]. MYC promotes the progression of liver cirrhosis by upregulating the inflammatory factors IL8, IL10, and TGFβ[18]. All of these previous reports were validated in our TF—miRNA—mRNA network.…”
Section: Discussionmentioning
confidence: 56%